Case Report: Clinical characteristics and genetic analysis of two patients with hereditary hemorrhagic telangiectasia - Wang, Qiu-Ying; Feng, Yu-Xuan; Zhu, Ying-Wei; Sun, Yu-Xia; Xu, Jing-Duan; Shi, Hui-Min; Mao, Yi-Min; Jiang, Hong-Wei (Frontiers in Genetics, 2022)
Objective: To analyze the clinical features and genetic characteristics of two patients with hereditary hemorrhagic telangiectasia (HHT) and to review the relevant literature. Methods: The clinical data of two HHT patients admitted to the author’s hospital between April 2019 and February 2022 were retrospectively analyzed. Meanwhile, the genetic analysis was performed with their consent. Results: The first patient was a 62-year-old woman who had been complaining of shortness of breath and fever for 20 days. Her previous medical history included brain abscess drainage and video-assisted thoracoscopic surgery for a pulmonary hemangioma. A right heart catheterization revealed no pulmonary arterial hypertension, and an abdominal enhanced magnetic resonance imaging revealed multiple arteriovenous malformations in the liver. Her ACVRL1 heterozygous variants were discovered through whole-exon gene testing. The second case involved a 47-year-old woman who had been experiencing chest tightness for the past 2 years. Several years ago, she underwent brain abscess drainage and embolization of a pulmonary arteriovenous fistula. Ultrasound revealed generalized hepatic vascular dilation, and enhanced computed tomography revealed numerous pulmonary venous fistulas scattered in both lungs as well as multiple arteriovenous malformations in the liver. Her whole-exon gene testing revealed that she, like her son, had heterozygous ENG variants. Conclusion: HHT patients may experience infection, bleeding, dyspnea, and other symptoms. Imaging is important in disease diagnosis and management because early detection and treatment can prevent major complications and disability or even death.